Interrogating ‘effectiveness’ in climate change adaptation: 11 guiding principles for adaptation research and practice - Singh, Chandni; Iyer, Soundarya; New, Mark G; Few, Roger; Kuchimanchi, Bhavana; Segnon, Alcade C; Morchain, Daniel (Informa UK Limited, 2022)
The Paris Agreement articulates a global goal on adaptation, which aims to ensure an ‘adequate adaptation response’ to the ‘global temperature goal’, and requires countries to report progress through periodic global stocktakes. However, there remain conceptual and methodological challenges in defining an adaptation goal and mixed evidence on what effective adaptation looks like and how it can be enabled. In this review, we demonstrate how different normative views on adaptation outcomes, arising from different epistemological and disciplinary entry points, can lead to very different interpretations of adaptation effectiveness. We argue that how effectiveness is framed will significantly impact adaptation implementation and outcomes. This, furthermore, represents a way of exercising influence in adaptation decision-making. Eleven principles of effective adaptation are distilled as a way to pluralize guidance in international processes such as the Global Stocktake as well as national and sub-national exercises on tracking and monitoring adaptation.